1999
DOI: 10.1093/jnci/91.9.772
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis and Growth Inhibition in Malignant Lymphocytes After Treatment With Arsenic Trioxide at Clinically Achievable Concentrations

Abstract: Substantial growth inhibition and apoptosis without evidence of differentiation were induced in most malignant lymphocytic cells treated with 1-2 microM As2O3. As2O3 may prove useful in the treatment of malignant lymphoproliferative disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
172
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(183 citation statements)
references
References 37 publications
10
172
0
Order By: Relevance
“…Resistance to chemotherapy is a major concern with the effective management of any cancer but is a particular concern with that of melanoma since malignant melanomas have high intrinsic resistance to chemotherapeutic-induced apoptosis (Soengas and Loewe, 2003). Studies have indicated resistance to the chemotherapeutic application of arsenic may be associated with increased levels of glutathione (Zhu et al, 1999). However, some studies have found no correlation between cellular glutathione content and arsenic sensitivity (Davison et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resistance to chemotherapy is a major concern with the effective management of any cancer but is a particular concern with that of melanoma since malignant melanomas have high intrinsic resistance to chemotherapeutic-induced apoptosis (Soengas and Loewe, 2003). Studies have indicated resistance to the chemotherapeutic application of arsenic may be associated with increased levels of glutathione (Zhu et al, 1999). However, some studies have found no correlation between cellular glutathione content and arsenic sensitivity (Davison et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Regardless as to whether basal glutathione levels are predictive of arsenic sensitivity, it is well established that the suppression of intracellular glutathione by inhibition of glutathione synthesis with buthionine sulfoximine (BSO) does potentiate the cytotoxicity of arsenic (Zhu et al, 1999;Davison et al, 2003;Kito et al, 2002). In the current study, suppression of glutathione in arsenite-resistant SK-Mel-3 and SK-Mel-28 rendered the cells sensitive to pharmacological arsenite concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…1,2-bis(O-aminophenoxy)ethane-N,N,NЈ,NЈ-tetraacetic acid tetracetoxymethyl ester (BAPTA-AM) was purchased from WAKO Pure Chemical Industries (Osaka, Japan). 3,3Ј-Dihexyloxacarbocyanine iodide [DiOC 6 …”
Section: Reagents and Antibodiesmentioning
confidence: 99%
“…Arsenic trioxide (As 2 O 3 ) was recently demonstrated to be an effective inducer of apoptosis in patients with relapsed acute promyelocytic leukemia (APL) and in patients with APL in whom all-trans-retinoic acid (ATRA) and conventional chemotherapy has failed. [1][2][3][4] Studies in vitro indicate that As 2 O 3 can induce apoptosis in myeloma cell lines, in plasma cells from myeloma patients, 5 in malignant lymphocytic cell lines 6,7 as well as primary cultures of lymphocytic leukemia and lymphoma cells, 6 in myeloid and B-cell leukemia cell lines, 8 in megakaryocytic leukemia cell lines, 9 in neuroblastoma cell lines 10 and in HPV16-immortalized human cervical epithelial cells. 11 The mechanism responsible for the induction of apoptosis has not been fully characterized, but As 2 O 3 induced apoptosis in NB4 cells, cloned from a relapsed patient with APL, by inducing loss of PML/RAR␣ protein 12 and by suppressing expression of the Bcl-2 protein.…”
mentioning
confidence: 99%
“…As 2 O 3 -induced apoptosis were accompanied by activation of death signals: caspase 3, 8 and 9 [10,11]. The generation of ROS appears to consistently accompany arsenic exposure and many evidences suggest that ROS may be a determinant of cellular susceptibility to arsenic [6,[12][13][14][15]. Manipulation of ROS may thus be a way to expend the anticancer therapeutic spectrum of As 2 O 3 .…”
Section: Discussionmentioning
confidence: 99%